Uji Aktivitas Antifungi Perasan Daun Kemangi (Ocimum sanctum Linn.) terhadap Aspergilllus terreus secara In Vitro [Antifungal Activity Test of Basil Leaves Juice (Ocimum sanctum Linn.) against Aspergilllus terreus by in Vitro] - Sudarno Sudarno; Tyfany Imanu Sabrina; Hari Suprapto (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Aspergillus terreus is a fungus that causes aspergillosis disease. The infected fishes showed grey white patches over the body. Haemorrhagic ulceratic patches were observed on the gill and skin. The infections resulted in the death of the fishes. The use of chemicals to control fungal attack A. terreus can harm fish, the environment and humans who eat them. Treatment of fungal diseases that use a lot of chemicals that can harm the fish, the environment and humans who eat them. The use of medicinal plants is a safe way to inhibit and kill fungus growth as well as environmentally friendly. One of them uses the basil plant (Ocimum sanctum). The purpose of this study was to determine the minimum concentration of activity and basil leaf juice (O. sanctum Linn) as antifungal against A. terreus growth in vitro . The experiment was conducted at the Laboratory of the Faculty of Fisheries and Marine Airlangga University in July 2013. The method used in this research that the paper disc diffusion method and diffusion pitting. The analysis used in this study is descriptive statistica. The results of research using the juice of basil leaves (O. santum) of juice concentration of 50% (2,5 ml juice of basil leaves + 2,5 ml NaCl) to concentration 100% (5 ml juice of basil leaves) did not produce a clear zone around the paper discs and pitting, it is the same as the negative control. The positive control did not show fungus growing on Sabouraud Dextrose Agar medium (SDA).